Efektivitas Kegiatan Inter Terminal Transfer Terhadap Throughput di KSO Tpk Koja - Diyanto, Faizal; Sihombing, Sarinah; Widyastuti, Sekar (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
Inter Terminal Transfer activities must be supported by Effective loading and unloading activities in order to maximize Throughput. The research objective in this study was to determine the effect of Inter Terminal Transfer and loading and unloading activities on Throughput at KSO TPK KOJA in 2019. This study uses primary data obtained from the results of respondents' answers by distributing questionnaires to employees. This research is a quantitative research by collecting The data is using the Likert scale, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing, both simple and multiple. Then the results obtained are if the Inter Terminal Transfer variable has a partial effect on Throughput, loading and unloading variables on Throughput, and the effect of Inter Terminal Transfer variables and loading and unloading variables jointly on Throughput variables. The results of the F test show that there is a significant regression effect of the Inter Terminal Transfer Variable (X1) and Loading and Unloading (X2) on the Variable Throughput (Y) KSO TPK KOJA in 2019.